Exploring the psychosocial needs of adults with haematological cancer under watch-and-wait - Russell, Katie (2023)
Background: Understanding patients’ unmet needs has been deemed critical for holistic cancer care provision. However, research reporting the unmet needs of individuals with haematological cancers under watch-and-wait (indolent haematological cancers [IHC]) is scarce, despite reports of high levels of psychological distress in this population. Therefore, the present study aimed to explore the psychosocial needs of individuals living with IHC and when these needs were met, if so at all. To further understanding, the study also aimed to explore if, and if so how, needs changed over a six-month period, and whether needs differed from those identified in individuals with prostate cancer under watch-and-wait.